Penguatan Jiwa Kewirausahaan Ibu Majelis Taklim melalui Kolaborasi Usaha di Kecamatan Lalembu Kabupaten Konawe Selatan - Palilati, Alida; Azis Muthalib, Dzulfikri; Rommy Suleman, Nursaban; Saleh, Salma; Mubaraq, Ahmad; Purwati Ningtyas, Ajeng (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
The Program for Strengthening the Entrepreneurial Spirit of Majelis Taklim Women through Business Collaboration in Lalembu District, South Konawe Regency, was implemented to enhance women’s awareness and economic skills through faith-based community empowerment. This activity employed a participatory approach through socialization, interactive workshops, and mentoring in forming business groups. The results showed an increase in participants’ understanding of entrepreneurship concepts, household business management, and the importance of group collaboration. Approximately 30% of participants began drafting simple business plans, such as producing cookies and handicrafts, and two majelis taklim-based business groups were formed with a commitment to developing local products. The success of this program was supported by active community participation, the role of majelis taklim leaders, and the availability of adequate facilities, while the main obstacles were limited access to digital technology and lack of organizational experience. This program not only improved participants’ knowledge and skills but also encouraged women’s economic independence and strengthened a culture of collaboration at the community level.